POLICY SIMULATION OF SEAWEED AQUACULTURE DEVELOPMENT IN KUPANG REGENCY, EAST NUSA TENGGARA PROVINCE BY HOUSEHOLD ECONOMICS APPROACH - Sunadji Sunadji; Agus Tjahjono; Harsuko Riniwati (Faculty of Fisheries and Marine Science, Brawijaya University, 2016)
This research to analyze alternative policies could be done to improve the income of seaweed farmers. The method is survey. Analysis of the data used simulation analysis policy. From the results, alternative policies could be done: a). rising labor costs 15%, the addition of one year of experience and the addition of long talus 15%, b). the addition of one year of experience, the addition of one year of education, and increasing the length of the talus 15%, c). rising labor costs 15%, the addition of one year of experience and the addition of one year of education, d). rising labor costs 15% and improving sanitation 5%, and e). the addition of one year of experience, the addition of one year of education and the addition of 5% level of cleanliness. The suggestions: a). to take the policy in a way to rising labor costs 15%, the addition of one year of experience and a 15% increase in length talus together, b). seaweed farmers need to be tested first, in order to determine the level of success of the policy alternatives, c). in the future the policy makers can simulate their own policy by using existing software. Keywords: Simulation, seaweed, aquaculture, policy, development